CRC handbook pf organic photochemistry and photobiology (Boca Raton, Florida, 1994)
The book is divided according to the chemical structure of the subtraste undergoing irradiation. It deals with hydrocarbons, oxygen-containing compounds, sulfur-containing compounds, nitrogen-containing compounds, and halogenated compounds
Keywords: photobiology - handboos, manuals, etc,photochemistry - handbooks, manuals, etc